The Role of Mental Health and Substance Use in Homeless Adults' Tobacco Use and Cessation Attempts. Issue 2 (3rd April 2019) - Harris, Taylor; Winetrobe, Hailey; Rhoades, Harmony; Wenzel, Suzanne
Abstract: Objective: Although tobacco use is prevalent among adults experiencing homelessness, research deficits exist regarding the mental health, substance use, and demographic correlates of tobacco use behaviors in this population. This study examined whether correlates of tobacco use among housed adults identified by the Center for Disease Control (CDC) were significant correlates of tobacco use and cessation attempts among a sample of homeless adults.Methods: Participants ( N  = 421) were adults experiencing homelessness entering permanent supportive housing programs in Los Angeles. Multivariate logistic regression determined associations of lifetime mental health diagnoses, recent substance use, demographic characteristics, and lifetime literal homelessness with daily tobacco use and cessation attempts.Results: Lifetime diagnoses of schizophrenia, posttraumatic stress disorder, depression, bipolar disorder, and illicit substance use were associated with increased odds of daily tobacco use. A lifetime diagnosis of depression was associated with an increased likelihood of a past 3-month tobacco cessation attempt, while illicit substance use was associated with a lower likelihood of a cessation attempt.Conclusions: Findings suggest that demographic and clinical characteristics associated with tobacco use differ among this sample of homeless adults and those identified by the CDC among housed adults. Mental health conditions and substance use appear to be the primary correlates of tobacco use among adults experiencing homelessness and may be critical in efforts aimed at improving cessation.